Villa Massimo 1986-1988 : Studiengäste und Ehrengäste der Villa Massimo, Rom, von 1986 bis 1988. - Becker, Wolfgang; Malangré, Kurt; Schwier, Hans; Schäuble, Wolfgang; Uelsberg, Gabriele; Wolken, Elisabeth; Wolken, Karl Alfred; Villa Massimo, Roma (Aachen : Neue Galerie - Sammlung Ludwig Aachen, 1989)
Adler, Jaroslav Ivan ; Beckschäfer, Max ; Bender, Hans ; Bollmann, Ekkehard ; Dahlem, Hans ; Denhoff, Michael ; Dublon, Kurt ; Erding-Swiridoff, Susanne ; Jakubaschke, Sigrun ; Kaesdorf, Julius ; Karkoschka, Erhard ; Krause, Karl-Heinz ; Kröhnert, Lilly ; Lange, Rudolf ; Maedebach, Mario ; Metzel, Olaf ; Meyer, Nanne ; Mohl, Heinz ; Neubauer-Woerner, Marlene ; Nöbel, Richard ; Ohff, Heinz ; Petzinka, Karl-Heinz ; Platschek, Hans ; Pods, Reinhard ; Prager, Heinz-Günter ; Runze, Ottokar ; Sattler, D.E. ; Schöpfer, Jo ; Soltau, Annegret ; Stroheker, Tina ; Telljohann, Peter ; Treichel, Hans-Ulrich ; Waller, Jürgen ; Westing, Giso ; Wickert, Erwin ; Zimmermann, Walter
Villa Massimo 1986-1988 : Studiengäste und Ehrengäste der Villa Massimo, Rom, von 1986 bis 1988, Neue Galerie - Sammlung Ludwig, Aachen, 8. September bis 12. November 1989
biografie
Duits
boek